Stochastic-Dynamic Limiting Pricing: An Empirical Test - Masson, Robert T.; Shaanan, Joseph (The Review of Economics and Statistics, 1982)
N the last decade several papers have enriched the theory of pricing. Kamien and Schwartz (1971), Gaskins (1971), Baron (1973), and Flaherty (1980)' have made major contributions with dynamic and stochastic models. They predict important new implications for pricing and afford an opportunity for more refined tests of this behavior. We test these new implications and provide additional confirmation of pricing. Insights into how our tests add to the evidence can be seen by briefly examining the theories and the earlier tests. Bain's (1956) static model predicts that monopolists in markets with high barriers to entry will limit to forestall entry, rather than charge a short-run maximizing price which would encourage entry and lead to lower future profits. It also predicts that monopolists facing low barriers will not price, because their opportunity cost of short-run profits forgone to forestall entry is great. When this opportunity cost exceeds the savings from reduced entry, firms prefer the short-run maximizing price. Conversely, when barriers are high, the opportunity cost of forestalling entry is low and firms price. The new models predict intermediate results. By definition, as price exceeds the level at which entry is forestalled, the entry rate or its probability increases above zero. The new theories assume that when price is slightly above the entryforestalling level, a flood of entry is not induced but a gradual increase in its rate or probability occurs. Firms may thus price to regulate the entry rate or probability, not forestall entry. Firms select intermediate prices, setting the marginal entry cost equal to the marginal benefit of a higher price. They reflect Bain's conclusions in the sense that when barriers are low, monopolists may charge high prices, letting entry erode future profits. However, if entry barriers are at intermediate levels, a monopolist's price may be lower. At yet higher barriers optimal prices climb, but often remain above the entry forestalling price.2 These models predict that many industries with high concentration would initially have high profits, but that entry would lead to reduced concentration and profits over time. This accords with Bain's (1970) finding that high concentration tends to erode over time and Brozen's (1971) finding that high profits in initially highly concentrated industries tend to erode over time. Many empirical cross-sectional studies show that measured profit rates are positively correlated with measures of structure-entry barriers and concentration (Weiss, 1974). A related literature has examined entry rates. Harris (1973) and Orr (1974) show entry rates rising as pre-entry profits are higher and falling as barriers are higher. Both the methodologies and the interpretations of the profit rate studies have been challenged. Brozen (1969, 1971) argues that with correct specification, they disintegrate. However, his tests would reject pricing if profits eroded over time as the new theories predict. Demsetz (1973) offers another rebuttal. He notes that firms in an industry may experience efficiencies (i.e., scale economies, superior inputs, or superior foresight). Superior firms will be winners in the market, earning higher profits and expanding their market shares. Industries with such superior firms would then be characterized by high concentration and high profits. Industries without such superior firms should have neither high profit rates nor high concentraReceived for publication April 1, 1981. Revision accepted for publication January 27, 1982. * Cornell University and Oklahoma State University, respectively. We are indebted to Joe Bain, William Greene, N. Kiefer. J. D. Rea, R. Reynolds, and anonymous reviewers for useful comments. Related results appear in J. Shaanan (1979). 1 A related set of extensions have posited other approaches to entry deterrence (Spence, 1977; Salop, 1979; and Kirman and Masson, 1980). 2 This is consistent with Gaskins (1970) but not Gaskins (1971), which is a special case in which fringe firms may be driven out.